A Multi-GNSS, Multifrequency, and Near-Real-Time Ionospheric TEC Monitoring System for South America - Mendoza, Luciano Pedro Oscar (2019)
Taking advantage of the public Global Navigational Satellite Systems (GNSS) infrastructure in South America, an operational monitoring system for the total electron content (TEC) in the ionosphere has been developed. It incorporates data in near real time, from more than 90 GNSS satellites tracked by more than 200 ground stations. In turn, the system produces every 15 min a snapshot, that is a map, of the current state of the regional ionosphere, which is immediately available online. These maps could be employed, for example, to augment positioning with single-frequency GNSS receivers. They could also be combined with similar products in order to obtain weighted and reliable regional TEC maps, even in near real time. Most importantly, these products could be employed as data input in space environment forecasting and nowcasting models, given their very short latency of just a few minutes. In order to assess the response of the whole system to severe geomagnetic disturbances, the performance of the whole monitoring system during an actual geomagnetic storm has been investigated. The results suggest that the near-real-time system should be quite capable to monitor the regional TEC at a high temporal rate even under such conditions.